The Influence of Ribbing of Mechanical Crank Press Cast C-Frames over the Stress State in Critical Areas - Pisarciuc, Cristian; Dan, Ioan; Cioară, Romeo (MDPI AG, 2022)
The research presented is directed to identify the ways to reduce stress state in critical areas of the C-frame of mechanical presses. Ribbing is a way to increase rigidity and a means to reduce energy consumption in operation. Hence, the objective is to design new frame models that would ensure that presented features are obtained. Starting from a reference model that was maintained as such, within the conducted study, an important part of the new solutions resulted by ribbing the lateral walls of the frame and determining three different distances between the ribs, as well as their various orientations. The finite element-FEM study of the resulted stress states was conducted for all devised models. FEA revealed that, in the new models with ribbed lateral walls, the maximum values of the stress have different evolutions for each of the three critical areas considered. In most new models, the maximum stress decreased by 2–5% in two of the critical areas and increased in the third. The study carried out allows the selection of the most performant of the new solutions and provides valuable information for application and further studies.
Keywords: C-frame; press; ribbing; stress; FEA